The Zika Virus Transmission Model - Jiraporn Lamwong; Puntani Pongsumpun (My University, 2017)
A mathematical model of Zika virus is studied in this paper.Zika is caused by Zika virus, a flavivirus related to yellow fever, dengue.In 1952, first outbreak occurred in Uganda.In 1962, an epidemic was recognized as the first time in Thailand.In this study, we consider the transmission cycle between two population groups: human and mosquito.Using standard dynamical modeling method, the stability conditions of our model is considered by Routh-Hurwitz criteria.The numerical simulations are shown to support the analytical results.
Keywords: Zika Virus; Mosquito-borne diseases and control